Ligas à base de ferro-titânio para aplicações de armazenamento de hidrogênio - Batista, Meigga Juliane Soares Mello (2018)
In the last decades, some countries have changed their energy matrix motivated by environmental and economic issues. Hydrogen (H2) stands out as a source of clean energy and your storage in the form of hydrides in metal alloys is promising. Among these, titanium-iron alloys (TiFe) present low cost and good cycling, but low absorption capacity and difficult activation. With addition of transition elements, H2 absorption occurs at room temperature, under moderate pressure and without the need for heat treatments for activation. In this work, vanadium (V) and zirconium (Zr) were added in the TiFe alloys to improve the absorption properties. For the production of the samples, electric arc fusion and mechanical grinding were used, with natural cooling and accelerated by suction casting. X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), X-ray Dispersive Energy Spectroscopy (EDS), Absorption and Desorption Kinetics Curves and Thermal Desorption Spectroscopy (TDS) were used for characterization. The samples with V were naturally cooled and exhibited H2 absorption capacity of between 0.9 and 1.9 wt%. However, the samples with Zr passed through the two cooling processes and demonstrated superior performance with maximum absorption of 2.0 and 2.2% for natural and accelerated cooling, respectively. Thus, addition of Zr proved to be more efficient than V and the rapid cooling technique decreased the time of absorption indicating to be a more advantageous process for the formation of hydrides.